WILLINGNESS TO COMMUNICATE IN ENGLISH OF UNIVERSITY STUDENTS IN TANGERANG SELATAN - Tryana Tryana; Lida Holida Mahmud (Universitas Pamulang, 2021)
The fact that Indonesian students’ reticent in speaking English is still found until today. Its phenomena commonly happens in English as a foreign language class. This pattern is related to students’ desires to speak up called Willingness to Communicate (WTC). Willingness to communicate concepts arise in individual’s L1 and L2. However, the present study explored some issues that emerge as a chance for foreign language learners to communicate. In particular, the study investigated an extent in which Indonesian EFL learners are eager to communicate in English. In addition, the study focuses on the correlation between willingness to communicate and language learning anxiety, language learning motivation. and situational influence. Furthermore, the study sees the correlation between willingness to communicate and gendre. The literature review focused on Maclyntre’s Heuristic model on willingness to communicate concepts. Then, It is linked to learning motivation and learning anxiety concepts in EFL class. The study involved a quantitative approach through employing 126 undergraduate students in Tangerang Selatan during the research phase of this project to generate survey data through questionnaires. Questionnaires that support the learner's willingness to communicate espoused from proposed. From the data analysis, it was found that there is correleation between anxiety, motivation and WTC in university students of Tangerang Selatan. However, the impact is low. There are other aspects influencing WTC that should be taken into consideration for further investigation. From the findings, it can be implied that eventhough learning anxiety appears on students learning, students motivation helps them to contend with their impartiality and proficiencies.